Sovereign rish in the Eurozone: a technical question? - Alonso, Nuria; Trillo, David (Papeles de Europa, 2015)
Since December 2009 until 2012 the euro area has shown a situation of strong economic uncertainty linked to government debt. The peripheral countries have had to adopt policies very similar to those of Latin Americans countries in the 80's, that have introduced additional pressure on the budget deficit of the countries mentioned in addition to generating a phase of stagnation with deflationary risk. During the call crisis of sovereign debt the government bond spread has been used as an indicator of sovereign credit risk, and as an excuse to implement austerity policies; now that there is an expectation of recovery of macroeconomic indicators and a low bond spread in countries like Spain, Ireland and Portugal, the opposite seems to be inferred: the sovereign risk has decreased. The problem of the debt crisis requires a multi-causal explanation must be linked to a set of decisions and actions of public and private institutions and not a conventional interpretation of the spread as risk premium. In the article we analyze the evolution of the spread in relationship with the actions of the European Commission and others institutions like European Central Bank and with different moments of international macroeconomic uncertainty.
Keywords: Public debt; spread; sovereign risk; credit risk; rating; crisis